Inductive effects in isolated molecules: 4-substituted bicyclo[2.2.2]octane-1-carboxylic acids - Exner, Otto; Böhm, Stanislav (Chemistry (Weinheim an der Bergstrasse, Germany), 2002)
Energies of sixteen 4-substituted bicyclo[2.2.2]octane-1-carboxylic acids, their anions, and pertinent 1-substituted bicyclo[2.2.2]octanes were calculated within the framework of density functional theory at the B3LYP/6-311 + G(d,p) level. Substituent effects were evaluated separately in the acid molecule and in the anion in terms of isodesmic homodesmotic reactions. In both cases, the substituent effects are proportional and of opposite sense, that in the anion being eight times greater; in the effect on acidity they are summed. The calculated acidities are in agreement with experimental values with a standard deviation of 1.1 kJ mol-1, and are recommended as a model for evaluating the inductive effect of various substituents, whether they are experimentally accessible or not. The resulting values are closely related to other scales but can be determined more reliably, particularly when compared with the previous quantum chemical method. We also checked electrostatic calculations and confirmed their very approximate character, particularly in the case of unsymmetrical substituents or of substituents with zero dipole moment.